Development of Novel Polypropylene Syntactic Foams Containing Paraffin Microcapsules for Thermal Energy Storage Applications - Francesco Galvagnini; Andrea Dorigato; Luca Fambri; Alessandro Pegoretti (Molecules, 2022)
polypropylene (PP) syntactic foams (SFs) containing hollow glass microspheres (HGMs) possess low density and elevated mechanical properties, which can be tuned according to the specific application. A possible way to improve their multifunctionality could be the incorporation of organic Phase Change Materials (PCMs), widely used for thermal energy storage (TES) applications. In the present work, a PCM constituted by encapsulated paraffin, having a melting temperature of 57 °C, was embedded in a compatibilized polypropylene SF by melt compounding and hot pressing at different relative amounts. The rheological, morphological, thermal, and mechanical properties of the prepared materials were systematically investigated. Rheological properties in the molten state were strongly affected by the introduction of both PCMs and HGMs. As expected, the introduction of HGMs reduced both the foam density and thermal conductivity, while the enthalpy of fusion (representing the TES capability) was proportional to the PCM concentration. The mechanical properties of these foams were improved by the incorporation of HGMs, while they were reduced by addition of PCMs. Therefore, the combination of PCMs and HGMs in a PP matrix generated multifunctional materials with tunable thermo-mechanical properties, with a wide range of applications in the automotive, oil, textile, electronics, and aerospace fields.